Comparative Genomic Sequencing and Pathogenic Properties of Equine Herpesvirus 1 KyA and RacL11 - Shakya, Akhalesh K.; O’Callaghan, Dennis J.; Kim, Seong K. (Frontiers in Veterinary Science, 2017)
Equine herpesvirus 1 (EHV-1) is a major pathogen affecting equines worldwide. The virus causes respiratory disease, abortion, and, in some cases, neurological disease. EHV-1 Kentucky A (KyA) is attenuated in the mouse and equine, whereas wild-type pathogenic strain RacL11 induces severe inflammatory infiltration of the lung, causing infected mice to succumb. The complete DNA sequencing of the KyA genome revealed that genes UL17 (ORF17), US6 (ORF73; gI), US7 (ORF74; gE), and US8 (ORF75; 10K) are deleted as compared to the RacL11 and Ab4 genomes. In-frame deletions in the US1 (ORF68), US4 (ORF71; gp2), and UL63 (ORF63; EICP0) genes and point mutations in 14 different open reading frames (ORFs) were detected in the KyA genome. Interestingly, UL1 (ORF1) and UL2 (ORF2) were deleted in both KyA and RacL11. Our previous studies showed that EHV-1 glycoproteins gI, gE, and full-length gp2 contribute to the pathogenesis of the RacL11 strain. The confirmation of these gene deletions in KyA suggests their contribution to the attenuation of this virus. The growth kinetics results revealed that KyA replicates to high titers in cell culture as compared to RacL11 and Ab4, indicating that the above genomic deletions and mutations in KyA do not have an inhibitory effect on KyA replication in cells of mouse, rabbit, equine, or human origin. Studies of EHV-1 pathogenesis in CBA mice showed that KyA is attenuated whereas mice infected with RacL11 succumbed by 3 to 6 days post-infection, which is consistent with our previous results.